Autoimmune thyroid disease is associated with a diagnosis of secondary Sjögren's syndrome in familial systemic lupus. Issue 3 (19th September 2006) - Hal Scofield, R; Bruner, Gail R; Harley, John B; Namjou, Bahram
Abstract : Background: Autoimmune thyroid disease is common in systemic lupus erythematosus (SLE). About 20% of patients with SLE have secondary Sjögren's syndrome. Methods: Families with more than one patient with SLE were identified. All patients met the revised classification criteria, although SLE-unaffected relatives were confirmed not to satisfy these criteria. Diagnosis of autoimmune thyroid disease and Sjögren's syndrome was made on the basis of a review of medical records, interview and questionnaire administered to patients with SLE, and by a questionnaire administered to SLE-unaffected subjects. Results: Of a total of 1138 patients with SLE, 169 had a diagnosis of Sjögren's syndrome. Of these 50 (29.6%) patients also had autoimmune thyroid disease. Of the 939 patients with SLE with no diagnosis of Sjögren's syndrome, 119 (12.7%) had autoimmune thyroid disease (χ 2  = 20.1, p = 0.000009). There was no association of a diagnosis of hypertension with secondary Sjögren's syndrome (42% vss 47%). Among 2291 SLE-unaffected relatives, 44 had diagnosed primary Sjögren's syndrome and 16 (36.3%) of these also had autoimmune thyroid disease. 265 of 2247 (11.8%) subjects had autoimmune thyroid disease but no Sjögren's syndrome (χ 2  = 24.2, p<0.001). Conclusions: Autoimmune thyroid disease is found in excess among patients with SLE with a diagnosis of secondary Sjögren's syndrome, as well as among their SLE-unaffected relatives with a diagnosis of primary Sjögren's syndrome.